National discrimination of minors citizens in the russian-occupied territories of Ukraine - Шпарага, Тетяна Іліодорівна; Михайленко, Тетяна Ігорівна (Київський національний університет імені Тараса Шевченка, 2025)
The article is devoted to the research of the general context of russia's policy of forced migration and deportation of Ukrainian children. It is emphasized that the deportation and forced migration of children have become a way of destroying Ukrainian identity and can be considered an act of genocide against the Ukrainian people. The main facts of the genocide are highlighted: the forced deportation of children and orphans, the separation of parents and children in filtration camps, which were accompanied by the transfer of children to the russian environment. The main groups of influence methods of the russian authorities on deported children are identified: psycho-emotional, “patriotic” and physical. The factors of influence of the environment of the aggressor state on the Russification of Ukrainian children are analyzed: learning the anthem and russian history, military clubs, agitation for admission to russian universities, rejection of everything Ukrainian, adoption by russian families, etc. Based on examples of violations of the rights of minors during a full-scale invasion, the main methods of russian influenceon Ukrainian children have been established. The influence of the Russian authorities is particularly detrimental to children, the most vulnerable age group in society. The return of children to their homeland in Ukraine is the responsibility of government agencies, public organizations and foundations.

Стаття присвячена дослідженню загальної картини щодо політики росії у примусовій міграції та депортації українських дітей. Висвітлено, що депортація та примусова міграція дітей стали способом знищення української ідентичності та може вважатися актом геноциду українського народу. Виокремлено основні факти геноциду: примусове вивезення дітей та дітейсиріт, розділення батьків та дітей у фільтраційних таборах, які супроводжувалися переміщенням дітей до російського середовища. Проаналізовано фактори впливу середовища держави-агресора на русифікацію українських дітей: вивчення гімну та російської історії, гуртки з військовим ухилом, агітація вступу до російських ВНЗ, відмова від усього українського, усиновлення російськими сім’ями тощо. Крім того, політика російської влади супроводжується порушеннями міжнародного гуманітарного права та прав людини. На основі прикладів порушення прав неповнолітніх осіб під час повномасштабного вторгнення встановлено основні методи впливу росіян на українських дітей. Особливо згубним вплив російської влади є саме на дітей – найбільш незахищену вікової верству суспільства.
Національна дискримінація неповнолітніх громадян на окупованих росією територіях України
Keywords: примусова міграція; геноцид; методи впливу російської влади; репатріація; інформаційна пропаганда; forced migration; child genocide; methods of influence of the russian authorities; repatriation; information propaganda